Royal society of Canada COVID-19 report: Enhancing COVID-19 vaccine acceptance in Canada - Noni E. MacDonald; Jeannette Comeau; Ève Dubé; Janice Graham; Margo Greenwood; Shawn Harmon; Janet McElhaney; C. Meghan McMurtry; Alan Middleton; Audrey Steenbeek; Anna Taddio (Canadian Science Publishing, 2021)
COVID-19 vaccine acceptance exists on a continuum from a minority who strongly oppose vaccination, to the "moveable middle" heterogeneous group with varying uncertainty levels about acceptance or hesitancy, to the majority who state willingness to be vaccinated. Intention for vaccine acceptance varies over time. COVID-19 vaccination decisions are influenced by many factors including knowledge, attitudes, and beliefs; social networks; communication environment; COVID-19 community rate; cultural and religious influences; ease of access; and the organization of health and community services and policies. Reflecting vaccine acceptance complexity, the Royal Society of Canada Working Group on COVID-19 Vaccine Acceptance developed a framework with four major factor domains that influence vaccine acceptance (people, communities, health care workers; immunization knowledge; health care and public health systems including federal/provincial/territorial/indigenous factors)-each influencing the others and all influenced by education, infection control, extent of collaborations, and communications about COVID-19 immunization. The Working Group then developed 37 interrelated recommendations to support COVID vaccine acceptance nested under four categories of responsibility: 1. People and Communities, 2. Health Care Workers, 3. Health Care System and Local Public Health Units, and 4. Federal/Provincial/Territorial/Indigenous. To optimize outcomes, all must be engaged to ensure co-development and broad ownership.